The Paradox of Indonesia’s Tobacco Excise Policy: A Literature Review of Effectiveness, Inequality, and Socioeconomic Impacts - Anshari, Khairullah; Subhan, Rizky; Noor, Riska Aulia; Fibriyanita, Fika (CV. Civiliza Publishing, 2025)
Indonesia’s tobacco excise policy has revealed a paradox between its normative objectives and the realities of its implementation. On one hand, the policy aims to reduce cigarette consumption and increase state revenue. On the other hand, successive excise tax hikes have triggered a rise in illicit cigarette circulation, undermined legal small-scale tobacco industries, and exacerbated socioeconomic inequality. This study employs a qualitative approach through literature review to examine the dynamics of tobacco excise policy using public policy theory, policy effectiveness, and socioeconomic disparity frameworks. The findings show that ineffective enforcement, weak distribution systems, and the absence of stakeholder inclusion have prevented the policy from achieving its intended outcomes. The sharp increase in excise taxes without sufficient oversight has created economic incentives for black-market activity, while also driving mass layoffs in small and medium-scale tobacco manufacturing. These outcomes confirm the theory of circular cumulative causation: policies that fail to integrate with social-economic realities tend to reinforce cycles of inequality and regulatory evasion. Therefore, a reformation of Indonesia’s tobacco excise policy is urgently needed—one that emphasizes fairness, effectiveness, and responsiveness through improved oversight, equitable fiscal distribution, and inclusive policymaking involving local communities and small businesses.